Studies on Growth Enhancement of Khejri (Prosopis cineraria (L.) Qruce) Seedlings and in situ Budded Plants - Purohit, A K; Samadia, D K; Pareek, O P (Annals of Arid Zone, 2016)
Studies were conducted on the growth vigor of khejri seedlings as affected by environment (in open and under shade net). irrigation method (rose can and mini-sprinkler). growth regulator treatment (50 ppm GA, 50 ppm GA + 2% urea. ]000 ppm MH and B-9) and on the growth of the in situ budded plants as affected by black polyethylene mulch and application of I L urea (2%) per plant under irrigated and rainfed conditions. Seedling height after 6 months was 34.33 cm in plants treated with 50 ppm GA when planted under open with rose can irrigation’ compared to 29.6 cm in the control. Linear growth of budded plants was 138.31 cm under rainfed conditions when mulched with black polyethylene compared to 76.98 cm in the control.